Dabo - Angeles, Sonny; Capul, Belina SB.; Flores, John Marin (Quezon City Philippine Information Agency [producer], 1989)
A documentary-drama on the pains and pleasures of growing up. Focus of the film is on problems in family relationship, particularly with parents, teachers and kins which sometimes lead to drug addiction and other social ills and vices.
Distributed by Felta Book Sales, Quezon City.
VHS.
Hero Bautista as Dabo ; Perla Bautista as Inay ; Fritz Gaston as Aboy ; Joel Michael Cabreros as Dolpo ; Dahde Salvador as Tonyo ; Gilbert de Leon as Pepol.
Keywords: Adult children -- Philippines; Drug addiction; Family -- Philippines